Causes for the Occurrence of Severe Drought at the Ogasawara (Bonin) Islands during the El Niño Event in 2018–2019 - Hiroshi Matsuyama (Atmosphere, 2024)
The Ogasawara (Bonin) Islands, consisting of more than 30 islands and located approximately 1000 km south of central Tokyo, occasionally experience severe droughts. Severe drought does not typically occur during El Niño (EN) events in the Ogasawara Islands because convective activity around the tropical western Pacific is inactive during EN events and correspondingly induces substantial precipitation around the Ogasawara Islands through the Pacific–Japan (P-J) pattern. However, a severe drought in 2018–2019 occurred during EN. In this study, we investigated the causes of drought occurrence. In 2018–2019, the El Niño Modoki (EN Modoki) event occurred simultaneously with EN, which decreased precipitation around the Ogasawara Islands from autumn to the following spring. This was induced by the positive sea level pressure anomaly and anticyclonic circulation around the Ogasawara Islands peculiar to the EN Modoki condition. In relation to the 2018–2019 drought, the investigation of past drought events at the Ogasawara Islands revealed that the drought in the spring and summer of 1991 also occurred during the simultaneous occurrence of the EN and EN Modoki events.